First Radio Astronomy Examination of the Low-Frequency Broadband Active Antenna Subarray - A. A. Stanislavsky; I. N. Bubnov; A. A. Konovalenko; A. A. Gridin; V. V. Shevchenko; L. A. Stanislavsky; D. V. Mukha; A. A. Koval (Advances in Astronomy)
We present the 25-element active antenna array and its remote control in the framework of the GURT project, the Ukrainian Radio Telescope of a new age. To implement beamforming, the array is phased with the help of discrete cable delay lines in analog manner. The remote control of the array is carried out through the paired encoder and decoder that can transmit parallel data about antenna codes serially. The microcontroller provides the online interaction between personal computer and beamformers with the help of the encoder-decoder system through wires or wireless. The antenna pattern has been measured by radio astronomy methods.